(E)-N'-(5-Bromo-2-hydroxybenzylidene)-3,5-dihydroxybenzohydrazide monohydrate - Saharin, S.M.; Ali, Hapipah Mohd; Khaledi, H. (International Union of Crystallography, 2010)
The Schiff base molecule in the title compound, C(14)H(11)BrN(2)O(4)center dot H(2)O, is almost planar with an r.m.s. deviation for the non-H atoms of 0.16 A. In the crystal structure, the Schiff base molecules and the water molecules are linked together by intermolecular N-H...O and O-H...O hydrogen bonds, leading to layers parallel to the bc plane. An intramolecular O-H...N hydrogen bond involving the imine N atom and a hydroxy substituent is also observed.